The Restorative Health Benefits of a Tactical Urban Intervention: An Urban Waterfront Study - Roe, Jenny; Barnes, Laura; Napoli, Nicholas J.; Thibodeaux, Jarrett (Frontiers in Built Environment, 2019)
Increasing access to urban waterfronts hold much promise for promoting healthy behaviors. While many US cities are revitalising their waterfronts, the health and well-being benefits associated with these urban design initiatives are largely unknown. Tactical urban interventions (such as parklets and pop-ups) are short-term projects that experiment with and gather input on potential urban design changes. To date, the effect of these projects on individual health outcomes has not been measured. This study reports a pilot quasi-experimental study which compares real-time exposure to an urban waterfront that was manipulated to provide a control versus an intervention ‘treatment’ condition that increased levels of comfort and fascination in the setting. Our study utilized a repeated-measures crossover randomized design and captured measures of stress and well-being whilst participants walked in each condition (n=23). First, real-time stress was captured using a smart watch to capture heart rate variability (HRV) during the walk, including for a resting baseline period of measurement pre-walk. Second, subjective mood (i.e. stress, arousal and hedonic tone) was assessed pre and post walk using the UWIST MACL Mood Scale (Matthews et al., 1990). Third, two measures of perceived restorativeness (i.e. fascination and being away) were captured pre and post walk using the PRS Scale (Hartig et al., 1997), together with two indicators of social well-being (i.e. place belonging and social trust). Results showed a statistically significant reduction in perceived stress from walking in the intervention, as compared to the control condition (p<0.05). This was matched by positive and statistically significant change on our measures of perceived restoration and social well-being from walking in the intervention. R¬esults showed an increase in parasympathetic response (as measured by HRV) from exposure to the intervention, indicating lower stress, and the opposite pattern whilst walking in the control condition (i.e. increased stress), albeit only significant at the 0.055 level. We discuss future directions for this type of experimental study design and how findings on short-term tactical urban designs could be usefully applied to direct longer-term urban design changes for public health gains.